Karakteristik bontot dengan kombinasi daging ikan payus (Elops hawaiiensis) dan ikan bulan-bulan (Megalops cyprinoides) - Ipat Kasyifatul Mufarihat; Sakinah Haryati; Aris Munandar (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Bontot is one of fish gel products in Banten Province. The main raw material of Bontot was Hawaiian ladyfish which is commonly found in the milkfish pond. However, the availability of the Hawaiian ladyfish was very limited. This study investigated the utilizaation of tarpon (Megalops cyprinoides), a fish of similar texture to the hawaiian ladyfish, for the production of bontot. The bontot quality was evaluated based on the organoleptic and microbial parameters. A combination of 37.5% ladyfish and 62.5% tarpon was considered as the best formula producing bontot with folding test 4.07 and bites 6.77, and the parameter of color, aroma, flavor, and texture similar to those of the commercial (3.43-4.00) products. The bontot contained moisture 50.50%, ash 2.42%, fat 0.32%, protein 5.67%, and carbohydrates 41.09% while the microbiological was below the 4.20 threshold, suggesting the bontot is safe for consumption.